SUPERCHANNEL SEBAGAI METODE CEPAT DALAM MENGATASI INTERFERENSI FREKUENSI 2,4 GHz - Sutiyo Sutiyo (Jurusan Teknik Informatika, 2011)
As a result of the release of ISM 2.4 GHz frequency for use in the field of wireless data communication through the media and the lack of clarity about the rules in the use of a frequency of 2.4 GHz to be one factor interference in wireless communication. Interference generally occurs in urban areas the level of use of wireless data communication through the media is very high. Wireless devices 2.4 GHz are easily available and inexpensive, making the user media data communications using wireless LAN as a cheap alternative compared to other data communication media, such as Fiber Optic, Radio Microwave Link.It is in fact the channel that is used in 2.4 GHz wireless communication is permitted only 11 channels starting from 2412Mhz-2462Mhz frequency, as more users make a frequency of 2.4 GHz increasingly crowded existing channels, resulting in wide bandwidth of each channel is also increasingly cramped. The width of the narrow bandwidth that clearly affects the quality of the process data communication, data sent or received experienced loss.One quick method to overcome these problems is to utilize the capabilities of wireless devices Superchannel. One of the wireless devices with Atheros AR5413 chipset which has a mini-PCI Superchannel is R52H which is the product of mikrotik. Superchannel frequency range starting from 2192Mhz - 2539Mhz. Indeed, in the frequency range is still illegal superchannel for some countries, like Indonesia, but many Internet access providers, or ISPs use this superchannel capabilities for data communication media, both for distribution to customers or to the ISP backbone network, although not used permanently.